2014
DOI: 10.1111/obes.12063
|View full text |Cite
|
Sign up to set email alerts
|

Unofficial Development Assistance: A Model of Development Charities’ Donation Income

Abstract: The empirical literature on the determinants of charities' donation income, distinguishing the charitable cause, is small. We consider the case of development charities specifically. Using a panel covering a quarter of a century, we observe a strong fundraising effect and a unitary household income elasticity. We find evidence that the conventionally identified 'price'effect may simply be the product of omitted variable bias. Our results further suggest that public spending on development crowds in private don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…One study performed by Roodman and Standley (2006) shows that a strong adverse effect of taxation on giving at an aggregated level but that comparison of 23 countries is based on some very unlikely assumptions, such as a very strong, positive income effect on giving that to a large extent has been proven wrong by other research. Other macro-level studies have shown that people do not give less during economic downturns, which is further evidence that having less money to spend does not make the public less willing to give per se (Arulampalam et al, 2009). The direct effects of tax reforms on disposable income therefore seem to have little consequence for charitable giving.…”
Section: Previous Researchmentioning
confidence: 90%
“…One study performed by Roodman and Standley (2006) shows that a strong adverse effect of taxation on giving at an aggregated level but that comparison of 23 countries is based on some very unlikely assumptions, such as a very strong, positive income effect on giving that to a large extent has been proven wrong by other research. Other macro-level studies have shown that people do not give less during economic downturns, which is further evidence that having less money to spend does not make the public less willing to give per se (Arulampalam et al, 2009). The direct effects of tax reforms on disposable income therefore seem to have little consequence for charitable giving.…”
Section: Previous Researchmentioning
confidence: 90%
“…Existing work does not directly test the mechanism responsible for these positive spillovers, but speculates that “fundraising of one charity may raise awareness of development issues and so increases donations made to all charities in the sector” (Arulampalam et al , 193). This assertion rests on empirical research confirming an association between awareness of need and donations of time and resources in a number of settings (Cheung and Chan ; Diamond and Kashyap ; Lee and Farell ).…”
Section: A Theory Of Capital Campaign Impactmentioning
confidence: 99%
“…This spillover effect has been observed for advertising expenditures in the private sector (for example, see Sahni ), and research in the nonprofit sector has recently demonstrated a similar result for fundraising expenditures. Examining donations to development organizations, Arulampalam, Backus, and Micklewright () found that an increase in the fundraising expenditures of the largest fundraisers leads to an increase in donations to other development charities. Specifically, they find that a 1 standard deviation increase in the fundraising expenditures of the largest development charities increases average donations to other development nonprofits by about 9 percent.…”
Section: A Theory Of Capital Campaign Impactmentioning
confidence: 99%